2015
DOI: 10.3310/hta191000
|View full text |Cite
|
Sign up to set email alerts
|

Optimal strategies for monitoring lipid levels in patients at risk or with cardiovascular disease: a systematic review with statistical and cost-effectiveness modelling

Abstract: BackgroundVarious lipid measurements in monitoring/screening programmes can be used, alone or in cardiovascular risk scores, to guide treatment for prevention of cardiovascular disease (CVD). Because some changes in lipids are due to variability rather than true change, the value of lipid-monitoring strategies needs evaluation.ObjectiveTo determine clinical value and cost-effectiveness of different monitoring intervals and different lipid measures for primary and secondary prevention of CVD.Data sourcesWe sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 231 publications
0
24
0
1
Order By: Relevance
“…To distinguish true change in HbA1c progression, we adapted a statistical method for distinguishing the properties of a test from the variability of its measurements; the methodology has been described in detail elsewhere [8][9][10]. Briefly, linear random effect models with random intercept and random slope, adjusted for gender and age at first measurement of HbA1c (continuous value), were used to derive parameters describing HbA1c progression.…”
Section: Calculating Signal and Noise For Laboratory Testingmentioning
confidence: 99%
“…To distinguish true change in HbA1c progression, we adapted a statistical method for distinguishing the properties of a test from the variability of its measurements; the methodology has been described in detail elsewhere [8][9][10]. Briefly, linear random effect models with random intercept and random slope, adjusted for gender and age at first measurement of HbA1c (continuous value), were used to derive parameters describing HbA1c progression.…”
Section: Calculating Signal and Noise For Laboratory Testingmentioning
confidence: 99%
“…Information is needed on when to start monitoring, when to stop monitoring, how frequently to monitor, what critical values are and how to respond to these values . CPGs should preferably include monitoring parameters that are specific, sensitive, accessible, affordable and applicable, and that provide early results to enable intervention . Previous studies by our group revealed that instructions for monitoring in Summary of Product Characteristics of (psychotropic) drugs in general were often found to be too ambiguous to be applicable in clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 CPGs should preferably include monitoring parameters that are specific, sensitive, accessible, affordable and applicable, and that provide early results to enable intervention. 12 Previous studies by our group revealed that instructions for monitoring in Summary of Product Characteristics of (psychotropic) drugs in general were often found to be too ambiguous to be applicable in clinical practice. 13,14 The applicability of monitoring instructions for patients using lithium in CPGs for treatment of BD is still unknown.…”
mentioning
confidence: 99%
“…To distinguish true change in HbA1c progression, we adapted a statistical method for distinguishing the properties of tests from the variability of measurements; the methodology has been described in detail elsewhere [25, 26]. Briefly, linear random effect models with random intercept and random slope, adjusted for gender, age and BMI at first measurement of HbA1c as continuous value, were used to derive parameters describing HbA1c progression.…”
Section: Methodsmentioning
confidence: 99%
“…We use the signal-to-noise ratio (SNR) as a quantitative marker to distinguish individuals with true HbA1c change from those with apparent change due to noise. Based on previous reports, we defined the minimal informative screening interval as the time at which the signal to noise ratio exceeds 1 [26, 27]. We calculated confidence intervals for these ratios through non-parametric bootstrapping (15,000 times).…”
Section: Methodsmentioning
confidence: 99%